The Effectiveness Of The Regulationn of The Head of The Police Security Manintance Agency Number 1 Of 2017 Concerning patrols To Prevent Criminal Actss Of Beating In The Beating In The Jurisdiction Of The Bali Police - I Komang Bagus Wi Suyasa; Nurianto Nurianto; Siti Nurmawan Damanik (Edunity Kajian Ilmu Sosial dan Pendidikan, 2024)
This study aims to analyze the effectiveness of the Chief of the Police Security Maintenance Agency Regulation Number 1 of 2017 concerning Patrols in preventing assault crimes within the jurisdiction of Bali Police. The main issue addressed in this research is the extent to which this regulation can reduce the incidence of assault crimes and the challenges encountered in its implementation.This research employs a qualitative method with a descriptive-analytical approach. Data were collected through in-depth interviews with police officers, document analysis, and direct observation. The data analysis was conducted by identifying patrol implementation patterns and measuring their success in preventing assault crimes.   The research findings indicate that the implementation of the Chief of the Police Security Maintenance Agency Regulation Number 1 of 2017 has been quite effective in reducing the incidence of assault crimes within the jurisdiction of Bali Police, although several challenges remain in its implementation, such as limited human resources and infrastructure to support patrols. The implications of this research suggest the need for enhancing personnel capacity and patrol facilities to improve the effectiveness of crime prevention. Additionally, recommendations for improving regulations and operational procedures are proposed to make them more adaptive to local conditions in Bali.